Disseminated Nontuberculous Mycobacterium Presenting as Chronic Diarrhea and Wasting - Manasi Singh MD; Marc Heincelman MD, MPH (SAGE Publishing, 2022)
Infections due to nontuberculous mycobacterium (NTM) are important in chronically immunosuppressed populations and are a particular threat to solid organ transplant recipients (SOT). However, they are not a common occurrence and have protean manifestations, making it important that clinicians maintain a high degree of suspicion in the correct patient population. Mycobacterium avium complex (MAC) usually presents with pulmonary involvement in immunocompetent population and disseminated disease in SOT patients with fever of unknown origin, lymphadenopathy, and cutaneous lesions being part of the well-known presentation. It is not commonly described as causing severe diarrhea. Here, we present an interesting case of a patient with a kidney and pancreas transplant who presented with debilitating wasting and chronic diarrhea. Biopsies and cultures confirmed MAC. To our knowledge, this is the first case report of MAC causing severe wasting diarrhea in renal transplant patients. The patient was treated with a multidrug regimen. Given the rare presentation of MAC presenting as chronic diarrhea, the treatment regimen is not standardized and infectious disease specialists should be involved early on. Up to 30% of renal transplant patients infected with NTM lose graft function and 20% die. Unfortunately, our patient suffered both these outcomes.